Relationship between perilipin genes polymorphisms and growth, carcass and meat quality traits in pigs. (30th March 2015) - Gol, S.; Ros‐Freixedes, R.; Zambonelli, P.; Tor, M.; Pena, R.N.; Braglia, S.; Zappaterra, M.; Estany, J.; Davoli, R.
Summary: The perilipins (PLIN) belong to a family of structural proteins that play a role regulating intracellular lipid storage and mobilization. Here, PLIN1 and PLIN2 have been evaluated as candidate genes for growth, carcass and meat quality traits in pigs. A sample of 607 Duroc pigs were genotyped for two single‐nucleotide polymorphisms, one in intron 2 of the PLIN1 gene ( JN860199:g.173G>A) and the other at the 3′ untranslated region of the PLIN2 gene ( GU461317:g.98G>A ). Using a Bayesian approach, we have been able to find evidence of additive, dominant and epistatic associations of the PLIN1 and PLIN2 polymorphisms with early growth rate and carcass length. However, the major effects were produced by the dominant A allele at the PLIN2 polymorphism, which also affected the carcass lean weight. Thus, pigs carrying an additional copy of the A allele at the g.98G>A PLIN2 polymorphism had a probability of at least 98% of producing carcasses with heavier lean weight (+0.41 kg) and ham weight (+0.10 kg). The results obtained indicate that the PLIN2 polymorphism could be a useful marker for lean growth. In particular, it may help to reduce the undesired negative correlated response in lean weight to selection for increased intramuscular fat content, a common scenario in some Duroc lines involved in the production of high quality pork products.